Analisis Komparasi Efektivitas Tayangan Iklan Televisi Situs Belanja Online Shopee Dan Tokopedia pada Masyarakat Kota Surabaya - Arofah, Nur; Pradipta, Ade Devia; Suryawati, I Gusti Agung Alit; Damasemil, Calvin (E-Jurnal Medium; Vol 4 No 2 (2023): Jurnal Ilmu Komunikasi Vol 4 No 2 Tahun 2023, 2023)
Television is one of the most common media for Indonesian citizens. Almost all citizens have television and at least watched television. There are varieties of content in television, and advertisement is one of the most seen contents. One of the most seen advertisements in television is online e-commerce advertisements. Some e-commerces that actively advertising through television are Shopee and Tokopedia. This study aims to compare the effectivity of Shopee and Tokopedia e- commerce Shopee and Tokopedia advertising in television to citizen in Surabaya. This study is using positivist paradigm with descriptive-quantitative method. This study is taking sample by using non- probability sampling and using purposive sampling method. Data was collected by distributing questionnaire. This study is using several analytical techniques to analyse the data, specifically by using arithmetic means analytical technique, and average difference T-test, and conclusion. This study shows different effectivity in Shopee and Tokopedia e-commerce advertising in television on Surabaya citizens. This study shows average score EPIC Model dimension where Shopee e- commerce advertisements excel Tokopedia e-commerce advertisement by 0,06. Keywords: Shopee, Tokopedia, Advertisement through Television, Surabaya Citizen.